Supplementation of Dried Mealworm (Tenebrio molitor larva) on Growth Performance, Nutrient Digestibility and Blood Profiles in Weaning Pigs - Jin, X. H. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2016)
This experiment was conducted to investigate the effects of dried mealworm (Tenebrio molitor larva) on growth performance, nutrient digestibility and blood profiles in weaning pigs. A total of 120 weaning pigs (28±3 days and 8.04±0.08 kg of body weight) were allotted to one of five treatments, based on sex and body weight, in 6 replicates with 4 pigs per pen by a randomized complete block design. Supplementation level of dried mealworm was 0%, 1.5%, 3.0%, 4.5%, or 6.0% in experimental diet as treatment. Two phase feeding programs (phase I from 0 day to 14 day, phase II from 14 day to 35 day) were used in this experiment. All animals were allowed to access diet and water ad libitum. During phase I, increasing level of dried mealworm in diet linearly improved the body weight (p<0.01), average daily gain (ADG) (p<0.01) and average daily feed intake (ADFI) (p<0.01). During phase II, ADG also tended to increase linearly when pigs were fed higher level of dried mealworm (p = 0.08). In addition, increasing level of dried mealworm improved the ADG (p<0.01), ADFI (p<0.05) and tended to increase gain to feed ratio (p = 0.07) during the whole experimental period. As dried mealworm level was increased, nitrogen retention and digestibility of dry matter as well as crude protein were linearly increased (p = 0.05). In the results of blood profiles, decrease of blood urea nitrogen (linear, p = 0.05) and increase of insulin-like growth factor (linear, p = 0.03) were observed as dried mealworm was increased in diet during phase II. However, there were no significant differences in immunoglobulin A (IgA) and IgG concentration by addition of dried mealworm in the growth trial. Consequently, supplementation of dried mealworm up to 6% in weaning pigs’ diet improves growth performance and nutrient digestibility without any detrimental effect on immune responses.